2016
DOI: 10.1039/c6cy02314b
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen-doped carbon nanotubes as efficient catalysts for isobutane dehydrogenation

Abstract: Large-scale production of isobutene from isobutane requires high-performance and cost-effective catalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The direct dehydrogenation of isobutane was conducted according to our reported method with modification. 34 Typically, 200 mg of catalyst was fixed on quartz-wool plugs in a conventional fixed-bed quartz tubular reactor of 8 mm inner diameter. The reaction temperature was set at 600 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The direct dehydrogenation of isobutane was conducted according to our reported method with modification. 34 Typically, 200 mg of catalyst was fixed on quartz-wool plugs in a conventional fixed-bed quartz tubular reactor of 8 mm inner diameter. The reaction temperature was set at 600 °C.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…In the C1s spectrum of N-SWCNTs-50 (Figure 2k), the peaks at 284.8, 285.1, 286.8 and 289 eV correspond to CC/CC, CO/CN, CO, and COC bonds, respectively. [34,35] Deconvolution of the N1s fine spectra leads to four types of nitrogenous substances: pyridine N (N-6, 398.1 eV), pyrrole N (N-5, 399.8 eV), quaternary N (N-Q, 400.8 eV) and pyridine-N-oxide (N-X, 402.5 eV) (Figure 2l). [34,36] It is previously indicated that N-5 and N-6 located at the edge of the carbon chain backbone can provide a certain pseudo-capacitance for supercapacitors.…”
Section: Resultsmentioning
confidence: 99%
“…The observed differences in product selectivity between the samples could be related to nitrogen‐containing groups, since the initial propylene selectivity decreases with increasing nitrogen content in all samples (Figure S9). Although the role of nitrogen functionalities in cracking reactions is not well understood, reduced selectivity due to cracking was previously reported over nitrogen‐doped carbons in the dehydrogenation of isobutane [25] …”
Section: Resultsmentioning
confidence: 99%